(3GbJUGOjGJ GdehGQO hGdHjFI (B/s - (3ebdO, QeVGf eMeOs; (3YGjO, YaGa YHO GdYRjR s ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3GbJUGOjGJ GdWGbI,GdehGQO GdRQGYjI hGdZPGFjI,GbJUGOjGJ GdehGQO GdHTQjI,eTcdI GdJdhK hGSJfRGa GdehGQOs
(3HHdjhZQGajG(B:(3U(B.399-400s
Keywords: (3GbJUGOjGJs; (3GdRQGYI(B-(3GbJUGOjGJs; (3GdUfGYI(B-(3GbJUGOjGJs